A Review of Medicinal Plants Traditionally used to Treat Male Sexual Dysfunctions – the Overlooked Potential of Acmella oleracea (L.) R.K. Jansen - Batista, Lecildo Lira; Nascimento, Lucas Corrêa do; Guimarães, Gabriel Francisconi; Pereira, Arlindo César Matias; Koga, Rosemary de Carvalho Rocha; Santos, Abrahão Victor Tavares de Lima Teixeira dos; Fernandes, Caio Pinho; Teixeira, Thiago Afonso; Hu, Yutao; Hu, Xuebo; Carvalho, José Carlos Tavares (Pharmacognosy Reviews)
Introduction: Male sexual dysfunctions are conditions of impaired sexual activity due to decreased sexual desire, impaired erection, or ejaculatory problems. These issues can hurt men’s quality of life by causing suffering, frustration, and sexual intimacy avoidance. Although many agents are available to treat such conditions, they are associated with relevant side-effects that could hamper the treatment, pointing to the need for novel agents to fill the gap of patients unable to have a satisfactory result. Methods: This review was performed by searching terms such as “medicinal plants” “Acmella oleracea (L.) R.K. Jansen or Spilanthes acmella auct. non (L.) Murr.”, together with “male sexual dysfunctions”, “hypoactive sexual desire disorder”, “erectile dysfunction”, and “premature ejaculation” on literature indexers such as PubMed, Scopus, and ISI Web of Science. Relevant literature from the articles’ references was also assessed. Results and Discussion: We reviewed a primer about male sexual dysfunctions (MSD); then, we describe some medicinal plants already used against MSD. Finally, some biological activities of Acmella oleracea are described, emphasizing its potential against MSD. Despite the importance of this medicinal plant for several activities, studies assessing its use for MSD are still lacking, even with convincing preliminary results reported. Overall, some plants have more robust scientific evidence, with randomized, placebo-controlled trials performed. Interestingly, although many plants’ activities are reported, very few studies assess their action mechanism, which is critical to understanding the more indicated occasions.
Keywords: Alkylamides; Premature Ejaculation; Erectile Dysfunction; Sexual Dysfunction; Phytotherapy.